G307 The intergenerational effects of war on the health of children. (7th April 2014) - Devakumar, D; Birch, M; Osrin, D; Sondorp, E; Wells, JCK
Abstract : Background: From physical injuries to mental scars, the adverse effects of war on the health of children have been well documented. Less well known is how exposure to war can propagate across generations, leading to morbidity in children yet to be born. Aims: To summarise the literature on the effects of war that endure to affect the next generation of children. Methods: Both published and grey literature were searched using the Medline, Embase and Psychinfo databases for the lasting effects of war. Where direct evidence was absent, we looked for evidence in similar non-conflict situations. Over 200 articles were reviewed and analysed. Results: There are numerous ways in which war can damage the health of children yet to be born, that mostly, though not exclusively, work via stresses to the mother. We collated evidence on four key areas: violence, mental health, infectious disease and nutrition, and considered how these may work in tandem. We also discussed the multiplicative effects of a predisposition to ill-health combined with on-going conflict when hostilities are prolonged. Conclusions: Research into the intergenerational effects of war is sparse, but as we have shown, an important factor to consider. We hope that the evidence laid out will stimulate research and contribute to the discussion of the costs of war; particularly in the longer-term in post-conflict situations in which interventions need to be sustained and adapted over many years. Based on the findings we suggest strategies to mitigate these long-lasting effects and recommend contemplating warfare through the lens of intergenerational justice, whereby those who resort to conflict should consider, and in some circumstances may be held accountable for, harms to the health of future generations.